2017
DOI: 10.3382/ps/pex018
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis s train specificity affects performance improvement in broilers

Abstract: The study reports the effects on broiler performance of a newly isolated Bacillus subtilis strain, which is phylogenetically not closely related to already well-described strains of B. subtilis. In the first experiment, birds were reared in battery cages and exposed to C. perfringens. An increase in growth performance was observed with the strain when compared to the challenged animals. Three additional growth trials were conducted to 35 d of age, in different rearing conditions (genetic breeds, corn-soybean m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 25 publications
1
31
0
1
Order By: Relevance
“…Generally, probiotics are used to help maintain a healthy microbial balance within the intestine to promote gut integrity and immune health. Probiotic bacteria can induce beneficial effects by producing antimicrobial substances such as SCFA and bacteriocins that limit the growth and survival of pathogenic microbes [ 77 ]. Notably, several strains of Lactobacillus have been found to lower the environmental pH through the production of lactic acid.…”
Section: Immunitymentioning
confidence: 99%
“…Generally, probiotics are used to help maintain a healthy microbial balance within the intestine to promote gut integrity and immune health. Probiotic bacteria can induce beneficial effects by producing antimicrobial substances such as SCFA and bacteriocins that limit the growth and survival of pathogenic microbes [ 77 ]. Notably, several strains of Lactobacillus have been found to lower the environmental pH through the production of lactic acid.…”
Section: Immunitymentioning
confidence: 99%
“…It is well known that gut health is a key point for animal performance due to its critical importance on nutrient digestion, absorption and metabolism, incidence of enteric diseases, and immune responses (Yegani and Korver 2008;Hamasalim 2016). Previous studies have shown that probiotics improved broilers' growth performance and promoted greater populations of symbiotic microbiota in the intestine of broilers (Mountzouris et al 2007;Latorre et al 2017;Rhayat et al 2017). In a recent study, Shah et al (2019b) found that supplementation of Lactobacillus bacteria increased intestinal villus' height and absorptive capacity in broiler chickens that led to higher final BW of the birds.…”
Section: Growth Performancementioning
confidence: 99%
“…It was reported that the effects of B . subtilis supplementation on growth performance and intestinal physiology in broilers were markedly strain-dependent 8 , 9 , providing a need for the continuous studies on the various strains of B . subtilis to understand their respective properties in animals.…”
Section: Introductionmentioning
confidence: 99%